Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1071/wf19066
|View full text |Cite
|
Sign up to set email alerts
|

Wildland fire emission factors in North America: synthesis of existing data, measurement needs and management applications

Abstract: Field and laboratory emission factors (EFs) of wildland fire emissions for 276 known air pollutants sampled across Canada and the US were compiled. An online database, the Smoke Emissions Repository Application (SERA), was created to enable analysis and summaries of existing EFs to be used in smoke management and emissions inventories. We evaluated how EFs of select pollutants (CO, CO 2 , CH 4 , NO x , total particulate matter (PM), PM 2.5 and SO 2 ) are influenced by combustion phase, burn type and fuel type.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 30 publications
(70 reference statements)
3
62
0
Order By: Relevance
“…This evaluation provides a hint that underestimates of aerosol emissions in GFED may be more specifically related to biases in the emission factors applied for aerosol species, instead of biases in satellite‐based fire detection, simulation of biomass, or parameterization of fuel consumption. Recent field measurements reported that the OA emission factors for North American wildfires are 2 to 4 times greater than those commonly used in global fire emission inventories (e.g., Liu et al, 2017; Prichard et al, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…This evaluation provides a hint that underestimates of aerosol emissions in GFED may be more specifically related to biases in the emission factors applied for aerosol species, instead of biases in satellite‐based fire detection, simulation of biomass, or parameterization of fuel consumption. Recent field measurements reported that the OA emission factors for North American wildfires are 2 to 4 times greater than those commonly used in global fire emission inventories (e.g., Liu et al, 2017; Prichard et al, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…They found similar results as the default temporal profile used here, but with an extended tail of fire activity into the evening/nighttime hours for western US forests. This result also illustrates how correcting one component in the smoke modeling calculation stream may not result in overall system improvement, due to compensating issues with other components, such as natural fuel heterogeneity (Drury et al 2014), fuel consumption algorithms (Prichard et al 2019), emission factors (Urbanski 2014, Prichard et al 2020, plume rise and the vertical allocation of emissions (Mallia et al 2018;Wilkins et al 2020), and interaction with the changing/diurnal boundary layer (Larkin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Biomass burning emission factors (EFs, g compound emitted per kg biomass burned) are a critical input to emissions inventories that are derived from vegetation/compound specific EFs and burned area, fuel consumption per unit area, or fire radiative power (Kaiser et al., 2012; Larkin et al., 2014; van der Werf et al., 2017). Global and regional emission estimates for biomass burning are subjected to large uncertainties, often at a factor of 4–10, given the difficulty of estimating burned area and fuel consumption (Carter et al., 2020; Pan et al., 2020; Zhang et al., 2014) along with large fire‐to‐fire variability and generally limited observational constraints in many wildfire‐prone regions, including the western U.S. (Jaffe et al., 2020; Prichard et al., 2020). For example, in a recent synthesis of field‐measured temperate forest EFs, many species that are important in plume SOA and O 3 formation such as furans and terpenes (Coggon et al., 2019; Hatch et al., 2019), have only been reported in seven western U.S. wildfires (Andreae, 2019; Friedli et al., 2001; Liu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%